STUDENTS’ PERCEPTION ON THE USE OF ENGLISH VIDEO BLOG TOWARDS THEIR SPEAKING PERFORMANCE - MOHAMMAD IQBAL (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This research presents the students’ perception on the use of English video blog toward their speaking performance. Since English has become an international language, students, especially those who use English as a foreign language, are required to be able to master and develop their English speaking skills. During this pandemic of Covid-19, students are required to be more active in practicing speaking English so that their speaking skills continue to improve. Thus, students are required to use one of the method that is flexible and easy to use anywhere and anytime. Therefore, the researcher then conducted a research with the aim to give a detail description of how are the students’ perception on the use of Englih video blog towards their speaking performance. In this study, the researcher used qualitative approach with descriptive qualitative design. The participants of this research were 10 students of fourth semester of English Department of University Islam Malang. The participants were chosen randomly. To explore the students’ perception on the use of English video blog towards their speaking performance, an online-based questionnaire and an online-based interview were used as the methods of collecting the data. The instruments used in this research were questionnaire and semi-structured interview which was adapted from (Safitri and Khoiriyah 2017). The questionnaire used in this research was using Likert Scale. The findings showed that there were some of the students who faced a problem about the pronunciation which made the participants difficult to convey the ideas when making videos. However, the participants did experience that the use of English video blog was helpful for their enhancement of speaking performance. In addition, the participants also argued that English vlog was very beneficial for the sutdents who wanted to improve their English speaking performance. All in all, the students have a positive perception on the use of English vlog as their learning media in improving their English speaking performance.